Assessment of mean testicular volume in adolescent school boys of Udaipur district (10–18 years) at different stages of pubertal development - Babani, Tarun; Goyal, Dileep; Sareen, Devendra (Indian Journal of Child Health, 2020)
Background: The most important changes during puberty are secondary sexual characters. Objective: The objective of this study was to find out the mean testicular volume (MTV) by Prader orchidometer at different stages of pubertal development. Materials and Methods: Children between 10 and 18 years of age (sample size 525) from schools of Udaipur city were included in the study. Children, who underwent major surgery or having any systemic disorders, were excluded from the study. TV assessment was done by Prader’s orchidometer with Tanner staging and correlation was statistically analyzed. Results: The maximum boys belonged to 15–16 years of age group (14.7%), and 9.3% of boys were in 10–11 years of age group. The secondary sexual characters were observed to increase with the increase in MTV. The MTV for P1 was 4.46 ml, for P5 was 22.68 ml, and for G1 and G5, it was 4.69 ml and 23.27 ml, respectively (p<0.05). Conclusion: TV adds more objectivity in the detection of sexual maturation and helps to differentiate early genital maturation than pubic hair. The study population had an early rise of TV before pubic hairs were clinically visible which showed that it was the first to increase with the onset of puberty.